FINANCING PRODUCT DIVERSIFICATION STRATEGY AND ITS IMPLICATIONS FOR PROFIT-AND-LOSS SHARING FINANCING CREDIT RISK (MUDHARABAH AND MUSYARAKAH CONTRACTS) - Ahmad Syukri; Meilita Tryana Sembiring; Fahmi Natigor (Journal of Accounting Research, Utility Finance and Digital Assets, 2026)
This study investigates the effectiveness of product diversification in managing credit risk in profit-and-loss sharing (PLS) financing at Bank Sumut Syariah. While Islamic banking theoretically leverages diversification for risk mitigation, akin to Modern Portfolio Theory, this research reveals an "Organizational Readiness Paradox": quantitative diversification has failed to effectively curb persistently high PLS risk. Using a qualitative descriptive-exploratory single case study approach, data were collected through in-depth interviews with 59 informants, field observations, and portfolio data analysis (2013–2024). Findings show that PLS non-performing financing consistently accounts for over 50% of total NPF and significantly exceeds consolidated NPF. This stems from a strategic gap between policy and portfolio reality, internal capability weaknesses (Human Resources 45.8%, Systems 28.8%), and misaligned incentive systems that prioritize volume over quality. The paradox underscores that elevated PLS risk is not inherent to Sharia contracts but rather reflects a mismatch between organizational capability and risk-sharing complexity. The study emphasizes the critical role of governance, robust Management Information System Early Warning System infrastructure, and adaptive human capital for effective diversification strategies.